Study on the Mechanism and Effect of a Partition Wall Controlling Foundation Pit Deformation in the Soft-Soil Area - Chunlei Feng; Dingli Zhang; Hualao Wang; Xuan Zhang (Advances in Civil Engineering)
Based on the soft-soil layer and several practical subway stations projects, the effect of partition wall main parameters on internal force and the deformation of retaining structure was thoroughly investigated via numerical simulation and orthogonal experiment. Results show that the influence of distance between partition wall and retaining structure, L, on controlling the internal forces of the retaining structure and maximum ground settlement, is more obvious; the maximum settlement can be reduced by more than 60%. Moreover, the influence of partition wall depth under the ground, H, within a certain range can substantially reduce the maximum lateral palisade structure; the lateral displacement can be reduced by about 50%; however, within the scope of the economic, the stiffness of the partition wall, E, with impact on retaining structure internal force and deformation is relatively weak. Finally, the applicability of the research results is verified.